Enhanced Performance of Nanocomposite Membranes by an Environmentally Friendly High-Pressure Silanization Method - Valenzuela-Bascunan, X; Rojas-Sepulveda, A (American Chemical Society, 2025)
Composite membranes that contain an inorganic phase dispersed in a polymer are valuable for various applications because they combine the flexibility of polymers with the excellent thermal stability and gas selectivity of inorganic materials. The appearance of voids at the interface between the organic and inorganic phases is a central issue in such nanocomposite design. One approach to tackling this issue is grafting the inorganic phase with silane coupling agents that serve as linkers for the two phases. The study reports the structural improvement of nanocomposite membranes by filler silanization in an environmentally friendly process. Silanization of silica nanoparticles with 3-aminopropyldiethoxymethylsilane was carried out by using supercritical carbon dioxide. The process based on supercritical solvent impregnation was designed to minimize the loss of nanoparticles and the generation of organic effluents. Surface-modified nanoparticles were obtained with grafting degrees of up to 18.7%. SEM imaging confirmed less prominent nanoparticle agglomeration after the modification. In the next step, nanocomposite membranes based on cellulose acetate (CA) (20 wt % nanosilica) and starch-chitosan blend (15 and 20 wt % nanosilica) were fabricated using solvent-casting. Dope solutions were prepared using neat and silanized nanosilica by employing an alternation of stirring and sonication. The membranes containing modified nanoparticles showed a more homogeneous structure. The silanization apparently improved the compatibility of the nanosilica with the polymers. Consequently, high-pressure hydrogen permeation through the nanocomposite CA-based membrane with 20 wt % modified nanoparticles was considerably reduced (93%) compared to the membrane with the pristine nanosilica. The oxygen barrier properties of the starch-chitosan blend were improved by 98.3% by adding 20 wt % of modified nanosilica, yielding a film with an oxygen permeability value as low as 0.007 cm3 mm/(m2 atm day). © 2025 The Authors. Published by American Chemical Society.